Analisis Faktor-Faktor Keberhasilan Perencanaan Pembangunan Berbasis Ekonomi Islam - Laiyinna Misqha Efendi; Mustika Ayu Anggreini; Rani Alfiani; Nurhayati Harahap (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
One tactic to achieve the goals this country seeks is economic growth. Economic development performance is measured based on a number of factors, including population growth, per capita income, unemployment, poverty level and balance of payments. However, in reality, this progress has not provided the best results because the community is still not the main beneficiary. Ultimately, all parties must rethink appropriate development plans to implement in our country considering the increasing rates of unemployment and poverty that are currently occurring. so that neglected communities no longer exist. Experts in the fields of economics, society and politics are starting to study how to achieve effective development without being plagued by unemployment and poverty. The interesting aspect of these studies actually comes from Muslim economists and thinkers. They present new options along with the development of new theories about Islamic economics. Adherents of sharia economics which are based on Islamic sharia principles are expected to behave professionally and demonstrate neatness, honesty, orderliness and regularity in their processes. This article aims to investigate how an Islamic economic perspective on development can address the problems of poverty, unemployment and equality, starting with the arguments given above.